Water-soluble highly charged fullerene derivatives as spherical electrolytes. Electrostatic contributions to thermodynamic functions of systems containing mixtures of counterions differing in charge and size - Škerjanc, Jože (Acta chimica slovenica, 2006)
The Poisson-Boltzmann equation has been solved to obtain the electrostatic potential for the spherical cell model of a fullerene molecule at which charged functional groups are attached. The fullerene macroion is surrounded by mixtures of small counterions differing in size and charge. The electrostatic internal and free energies, degree of binding of counterions, osmotic coefficient, and distribution of counterions around the charged fullerene shell are calculated. These properties are presented as functions ofradii, charges and mole fractions of counterions.
Keywords: elektroliti; elektrostatski potencial; fizikalna kemija; fulereni; modeli; osmoza; Poisson-Boltzmannova enačba; raztopine; termodinamika